Successful Groin Flap for Dorsal Hand Defect in Elderly Patient with Comorbidity - A. Hakami (Вестник хирургии имени И.И. Грекова)
The pedicled groin flap is an effective and adaptable method for covering wounds on the hand and distal forearm. This approach offers reliable results and is less complex and time-consuming than free-tissue transfer. Despite the common belief that the groin flap should be avoided in elderly patients due to the risk of shoulder stiffness, we found success-ful outcomes in a 93-year-old woman with type 2 diabetes mellitus, arterial hypertension, rheumatoid arthritis, and a history of bilateral hip TEP surgeries in 2009 and 2007. Immediate shoulder mobilization and ongoing physical therapy during the flap maturation and pedicle division phases were crucial in achieving these favorable results. This case report was performed in Department of plastic, reconstruction and Hand surgery, University hospital Magdeburg, Germany.